The Gospel According to Science Fiction : From The twilight Zone to the Final Frontier - Mckee, Gabriel, 1979- (Louisville : Westminster John Knox Press, 2007)
Explores the theological nature of science fiction, drawing on examples from television, literature, and films to explain how science fiction can help people understand not only who they are but who they will become.
Includes bibliographical references (p. 269-282) and index.
Keywords: Science fiction, American -- History and criticism; Science fiction, English -- History and criticism; Science fiction films -- History and criticism; Religion in literature; Religion in motion pictures; Faith in literature